Simulation of Electrochemical Processes III 2009
DOI: 10.2495/ecor090161
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of mild steel and 316L austenitic stainless steel with different surface roughness in sodium chloride saline solutions

Abstract: The corrosion behaviour of mild steel and 316L austenitic stainless steel was investigated in saline solution containing 1 and 3%NaCl. Specimens with surface roughness of 200, 600 grit emery paper and 1μm diamond paste were investigated. The anodic polarization measurement technique was performed at a scan rate of 1mV/s for a fixed period of 1 hour. The experimental results revealed that chloride ions have a significant effect on the corrosion behaviour of both steels as expected. As the surface roughness of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…At the same time, it is necessary to consider that surface finishing significantly influences the localized corrosion resistance of these metallic materials in chloride environments, as reported by the present authors [5,6] and by many other authors [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In particular, there is a certain agreement among them on the relationship between pitting potential and surface roughness, expressed in terms of Ra and Rz parameters, when the surface of the samples is treated by different technological processes or when 2 of 12 samples are submitted to a grinding operation producing the same surface finishing but different roughness [5,6,[13][14][15][16]. In details, Rz is the sum of the height of the highest peak and the absolute depth of the deepest valley of the roughness profile, whereas Ra is the average of the ordinates of this profile (UNI EN ISO 4287:2002 standard).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…At the same time, it is necessary to consider that surface finishing significantly influences the localized corrosion resistance of these metallic materials in chloride environments, as reported by the present authors [5,6] and by many other authors [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In particular, there is a certain agreement among them on the relationship between pitting potential and surface roughness, expressed in terms of Ra and Rz parameters, when the surface of the samples is treated by different technological processes or when 2 of 12 samples are submitted to a grinding operation producing the same surface finishing but different roughness [5,6,[13][14][15][16]. In details, Rz is the sum of the height of the highest peak and the absolute depth of the deepest valley of the roughness profile, whereas Ra is the average of the ordinates of this profile (UNI EN ISO 4287:2002 standard).…”
Section: Introductionmentioning
confidence: 63%
“…Therefore, it can be considered that when the passivity film on AISI 430 is damaged, there is a very low possibility for this material to return passive and, at the same time, there is a high probability to show corrosion phenomena, independently from roughness. In order to make an in depth study on the relationship between localized corrosion resistance of SSs and roughness parameters, some authors tried to correlate the E pit −E corr differences (as a measure of the "extension of passivity range", in terms of potentials) with Ra and Rz, obtaining controversial results [8,10,14]. In the present work, a different approach has been used following literature findings [28], from which E pit −E prot differences were considered for measuring the extension of the hysteresis loops of the anodic CPP curves.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the general and localized corrosion behaviour of alloys depends on their roughness and passivation behaviour. The effect of surface roughness has been investigated on both localized and general corrosion of different metals such as stainless steel, copper, aluminium, magnesium, titanium and mild steel [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al have reported that the corrosion rate of carbon steel increases with the surface roughness [11] while Li and Li also found that the EWF fluctuation of copper increases with an increase in roughness which may promote the formation of corrosion cell [5]. Also Abosrra et al reported that, as the surface roughness of 316L stainless steel increased, the breakdown potential, the free corrosion potential and the width of passivity decreased, hence leading to an increase in corrosion rate [12]. However, in the case of mild steel specimens, it has been shown that improving surface finish leads to an increase in corrosion rate [12].…”
Section: Introductionmentioning
confidence: 93%
“…Also Abosrra et al reported that, as the surface roughness of 316L stainless steel increased, the breakdown potential, the free corrosion potential and the width of passivity decreased, hence leading to an increase in corrosion rate [12]. However, in the case of mild steel specimens, it has been shown that improving surface finish leads to an increase in corrosion rate [12]. Other studies have found the effect of surface roughness is marginal compared to effect of residual stress [13,14].…”
Section: Introductionmentioning
confidence: 97%